Heinz Mack - Korrespondenzen 1957-2016 - Eggeling, Ute 1955-; Beck, Michael 1960-; Mack, Valeria (Beck & Eggeling Kunstverlag, 2016)
On the occasion of Heinz Mack's 85th birthday, Beck & Eggeling is presenting the solo-exhibition 'Korrespondenzen'. Works by the artist's ZERO-era will be exhibited alongside works from his later career and most recent pieces, giving the viewers the possibility to discover relations and connections between works of all of Mack's creative periods. 0For more than 60 years German artist Heinz Mack is working as a painter and sculptor. During this time Mack created an oeuvre in which he continuously involves light as a central artistic element. "Light is determining for my art. As far as light is concerned, I want to push the limits of what is possible", says the artist. His oeuvre compromises sculptures, paintings, drawings, prints and photography. Futhermore, Mack creates works for the public space, such as the impressive installation 'The Sky Over Nine Columns', which - realised by Beck & Eggeling - was shown in Venice during the Architecture Biennial in 2014 and is currently on view in Instanbul. The installation will travel to Valencia in summer and Sankt Moritz in winter 2016
Ausstellung Heinz Mack. Korrespondenzen, 8. April - 4. Juni 2016, Beck & Eggeling, Düsseldorf. - Reihentitelzuordnung duch Verlagsmitteilung
Keywords: Mack, Heinz -- 1931-; Ausstellungskatalog -- Beck & Eggeling International Fine Art -- 08.04.2016-04.06.2016 -- Düsseldorf; Ausstellungskatalog -- Beck & Eggeling International Fine Art -- 23.09.2016-12.11.2016 -- Wien